Digging deeper : investigations into rocks, shocks, quakes, and other earthy matters - Markle, Sandra (Lothrop, Lee & Shepard Books, 1987)
Discusses various aspects of geology, such as plate tectonics, erosion, and mineral resources. Includes related experiments and activities.